Semantic Series as a Discourse Analysis Tool (Discourse about Generations) - N. V. Orlova (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The question of methods of discourse semantics modeling, understood as a content-thematic community of texts, is considered. The novelty of the research is seen in the expansion of the methodological tools in the study of discourse as an array of texts, in the refinement of supra-individual knowledge about an important social phenomenon. The relevance of the study is due to the interest of the humanities in the theory of generations, which has not yet received a linguistic response. Attention is paid to the ideas and techniques that make it possible to derive text-discursive meanings on the basis of isotopy and related concepts, in particular the concept of a semantic series. The construction of semantic series as a proven technique for analyzing literary texts is extrapolated to the study of discourse formed by a collective speech subject, which is the author’s version of the presentation of speech systemicity. The semantic series identified in the aggregate of fragments of different types of texts containing the lexeme generation are analyzed. Attention is paid to the series that objectify such semantic blocks as self-presentation of subjects of speech by belonging to a generation, categorization of generations, generational values. The author compares the meanings, actualized by the semantic series, with the provisions of the interdisciplinary theory of generations, developed by N. Howe and W. Strauss, proves a partial intersection of theoretical provisions and everyday ideas.